PENGARUH SISTEM PENGENDALIAN INTERNAL DAN KEKUATAN KOERSIF TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - S Purnomo, Budi (Program Studi Akuntansi FPEB UPI, 2014)
This research aims to empirically examine the effect of the internal control system and the coercive force of the quality of local government financial reports. The method used is descriptive method of verification. While the technique of data analysis using correlation coefficient analysis and coefficient of determination. Quantitative data is secondary and primary data. Secondary data in the form of examination reports on the financial statements of local government district / city in the first Bogor region of West Java province in 2012 were obtained from Badan Pemeriksa Keuangan (BPK). Sementara data primer dikumpulkan dari kepala seksi akuntansi pada pemerintah daerah kabupaten/ kota di wilayah I Bogor provinsi Jawa Barat. The results showed that the internal control system is not a positive influence on the quality of financial reports of local governments while the coercive power of positive influence on the quality of local government financial reports.